High-weather-resistance perovskite battery
By introducing the HALS-770 intermediate layer and optimized layer structure into the perovskite battery, the problems of instability and short life of perovskite battery in harsh environments are solved, and higher stability, photoelectric conversion efficiency and Weather resistance.
Patent Information
- Application Number
- CN202411512499.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
AI Technical Summary
Traditional perovskite batteries exhibit instability and short life in harsh environments such as high temperature, high humidity, and ultraviolet radiation, which limits their durability in practical applications.
Using the HALS-770 intermediate layer and optimized layer structure, including the bottom layer, perovskite active layer, HALS-770 intermediate layer, electron transport layer, buffer layer and electrode deposition layer, the oxidation and hydrophobicity of the HALS-770 layer is improved The antioxidant, heat and water stability of perovskite batteries.
It significantly improves the stability and photoelectric conversion efficiency of perovskite batteries, extends the service life of the equipment, and enhances its weather resistance in harsh environments.
Smart Images

Figure HDA0005105815970000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of perovskite batteries, and in particular to a highly weather-resistant perovskite battery. Background Art
[0002] High-weather-resistant perovskite cells are an advanced photovoltaic technology developed specifically to enhance the stability and life of perovskite solar cells in harsh environments. Traditional perovskite cells have rapidly emerged in the photovoltaic field due to their high efficiency and low cost, but the chemical instability of their materials limits their durability in practical applications. To this end, improving the performance of perovskite cells under harsh conditions such as high temperature, high humidity, and ultraviolet radiation has become a research focus, which has promoted the development of high-weather-resistant perovskite cells.
[0003] Development status of high weatherability perovskite technology:
[0004] The research and development of highly weather-resistant perovskite cells mainly focuses on material modification, interface engineering, and packaging technology. In recent years, by introducing new perovskite materials, optimizing battery structure, and adopting advanced packaging technology, researchers have made significant progress in improving the environmental stability and anti-attenuation performance of perovskite cells. At present, a number of technological breakthroughs have greatly improved the service life of perovskite cells, making them more competitive in practical applications.
[0005] Key technologies of high weather-resistant perovskite technology:
[0006] Material modification: One of the core elements of high weatherability perovskite cells is the modification of perovskite materials. By introducing organic or inorganic cations with stronger moisture resistance to replace the traditional combination of methylamine (MA) and lead iodide (PbI2), such as formamidine (FA) or inorganic cations (such as cesium Cs+) and halogen anions (such as chlorine Cl-, bromine Br-) to form a more stable perovskite structure. This material modification effectively improves the heat resistance and moisture resistance of the perovskite layer, and slows down the damage to battery performance caused by environmental factors.
[0007] Interface engineering: Interface engineering is also a crucial technology in highly weather-resistant perovskite cells. By optimizing the chemical properties and physical contacts of the interfaces of each layer in the battery, the energy loss and charge recombination at the interface can be reduced, and the efficiency and stability of the battery can be improved. Specific methods include introducing interface modifiers such as organic molecules, self-assembled monolayers (SAMs) or two-dimensional materials (such as graphene) between the perovskite layer and the transport layer. These modifiers can effectively prevent the penetration of moisture and oxygen, thereby enhancing the environmental tolerance of the battery.
[0008] Advanced packaging technology: Improvements in packaging technology are crucial to improving the weather resistance of perovskite cells. Highly weather-resistant packaging materials and processes can not only effectively isolate moisture and oxygen from the external environment, but also protect perovskite materials from damage by ultraviolet radiation. Common packaging technologies include multilayer polymer film packaging, glass packaging, and flexible packaging technology. These packaging methods enhance sealing and durability, making perovskite cells more stable in harsh environments. Summary of the invention
[0009] In order to overcome the above-mentioned defects of the prior art, the present invention provides a highly weather-resistant perovskite cell, which improves the stability and photoelectric conversion efficiency of the perovskite cell and enhances its antioxidant and heat resistance.
[0010] In order to achieve the above-mentioned purpose of the invention, the present invention provides a highly weather-resistant perovskite battery, wherein the perovskite battery comprises a bottom layer, a perovskite active layer, a HALS-770 intermediate layer, an electron transport layer, a buffer layer and an electrode deposition layer, wherein the perovskite active layer is arranged on the bottom layer, the electron transport layer is arranged on the perovskite active layer, the buffer layer is arranged on the electron transport layer, the electrode deposition layer is arranged on the buffer layer, and the HALS-770 intermediate layer is arranged on the electrode deposition layer.
[0011] Furthermore, the preparation method of the bottom layer includes:
[0012] Substrate pretreatment: Place the ITO / glass substrate in an ultrasonic bath of deionized water, ethanol, acetone, and isopropanol in sequence for 15 minutes each time;
[0013] After cleaning, the ITO / glass substrate was treated in UV-ozone for at least 15 min to remove organic contaminants on the surface;
[0014] Prepare PTAA solution: dissolve 5 mg / ml PTAA in chlorobenzene and add 25 wt% F4-TCNQ for doping;
[0015] Spin-coat the PTAA solution on the treated ITO / glass substrate surface at a speed of 4000 rpm for at least 30 seconds;
[0016] After spin coating, the ITO / glass substrate was annealed at a temperature of 100° C. for at least 15 minutes.
[0017] Furthermore, the method for preparing the perovskite active layer includes:
[0018] A mixed precursor solution of 1.3 mol PbI2 and 0.3 mol MAI was prepared in DMSO and DMF;
[0019] The precursor solution was spin-coated on the HTL surface at 6000 rpm for 15 s;
[0020] Then, a 40 mg / ml MAI solution was spin-coated in isopropanol at a speed of 4000 rpm for at least 45 seconds;
[0021] After spin coating, annealing was performed in air for 30 minutes.
[0022] Furthermore, the preparation method of the HALS-770 intermediate layer includes:
[0023] HALS-770 was dissolved in toluene at a concentration of 1.5 mg / ml;
[0024] The solution was spin-coated on the perovskite film at a speed of 6000 rpm for at least 30 seconds;
[0025] After spin coating, anneal at 80 °C for at least 3 min.
[0026] Furthermore, the preparation method of the electron transport layer and the buffer layer includes:
[0027] Prepare PC61BM solution: dissolve 20 mg / ml PC61BM in chlorobenzene;
[0028] Spin-coat the PC61BM solution on the perovskite layer at a speed of 2700 rpm for at least 30 seconds to form an electron transport layer;
[0029] Prepare BCP solution: dissolve 0.5 mg / ml BCP in isopropanol;
[0030] The BCP solution was spin-coated on the PC61BM layer at a speed of 6000 rpm for at least 30 seconds to form a buffer layer.
[0031] Furthermore, the preparation method of the electrode deposition layer includes: depositing a silver electrode on the BCP layer by thermal evaporation, and controlling the vacuum degree at 5.0×10 -4 Below Pa.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 4. Improved stability:
[0034] The unencapsulated device retained more than 95% of its initial efficiency after being stored for 30 days under ambient conditions (humidity of approximately 25-50%).
[0035] In the maximum power point tracking (MPPT) test in the glove box, the device's T80 (time to maintain 80% of initial efficiency) exceeded 1400 hours, significantly higher than the original device;
[0036] Compared with untreated perovskite films, HALS-770 modified perovskite films have reduced surface defects, reduced non-radiative recombination, and improved carrier extraction and transport efficiency;
[0037] 5. Improved photoelectric conversion efficiency:
[0038] Pin structure perovskite solar cell using HALS-770 at 0.06cm 2 A photoelectric conversion efficiency (PCE) of 21.88% was achieved on an effective area of 1.50 m2.
[0039] At 4cm 2 On the effective area, the PCE of the perovskite solar module reached 19.07%;
[0040] The PCE of the nip structure device using HALS-770 is also significantly improved, 0.06cm 2 and 1.0cm 2 The devices achieved PCEs of 23.03% and 20.73%, respectively;
[0041] 6. Enhanced antioxidant and heat resistance:
[0042] The HALS-770 layer enhances the antioxidant capacity of the perovskite by forming NO· radicals, which react with superoxide (O2·-), thereby removing O2·-;
[0043] The HALS-770 layer prevents the volatilization of organic cations and the migration of Ag+ and I-, improves the thermal stability of the perovskite and slows down the destruction of the Ag electrode;
[0044] Thermal stability tests show that the HALS-770 modified perovskite film maintains good structure and performance after continuous annealing at 85°C for 56 days;
[0045] 7. Enhanced water stability:
[0046] Water contact angle tests and water stability tests showed that HALS-770 modified perovskite films exhibited better stability in water and water vapor exposure;
[0047] The hydrophobic alkyl chain of HALS-770 and the hydrophilic ether and carbonyl groups work together to increase the hydrophobicity of the perovskite film. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 is a schematic cross-sectional structural diagram of an embodiment of the present invention; DETAILED DESCRIPTION
[0049] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the invention, rather than all the embodiments. The embodiments of the present invention are described below in conjunction with the drawings.
[0050] like Figure 1 As shown, a highly weather-resistant perovskite battery includes a bottom layer 1, a perovskite active layer 2, a HALS-770 intermediate layer 6, an electron transport layer 3, a buffer layer 4 and an electrode deposition layer 5, wherein the perovskite active layer 2 is arranged on the bottom layer 1, the electron transport layer 3 is arranged on the perovskite active layer 2, the buffer layer 4 is arranged on the electron transport layer 3, the electrode deposition layer 5 is arranged on the buffer layer 4, and the HALS-770 intermediate layer 6 is arranged on the electrode deposition layer 5;
[0051] The following is the preparation method of each layer. By stacking them layer by layer on the ITO / glass substrate, a highly weather-resistant perovskite cell is formed. The specific preparation methods of each layer are as follows:
[0052] The preparation method of the bottom layer 1 comprises:
[0053] Substrate pretreatment: The ITO / glass substrate was cleaned by placing it in an ultrasonic bath of deionized water, ethanol, acetone, and isopropanol in turn for 15 minutes each time;
[0054] After cleaning, the ITO / glass substrate was treated in UV-ozone for at least 15 min to remove organic contaminants on the surface;
[0055] Prepare PTAA solution: dissolve 5 mg / ml PTAA in chlorobenzene, where PTAA is poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], and add 25 wt% F4-TCNQ for doping;
[0056] Spin-coat the PTAA solution on the treated ITO / glass substrate surface at a speed of 4000 rpm for at least 30 seconds;
[0057] After spin coating, the ITO / glass substrate was annealed at 100°C for at least 15 minutes to form a bottom layer 1;
[0058] The preparation method of the perovskite active layer 2 comprises:
[0059] A mixed precursor solution of 1.3 mol PbI2 and 0.3 mol MAI was prepared in DMSO and DMF, where PbI2 was potassium iodide, MAI was methylammonium iodide, DMSO was dimethyl sulfoxide, and DMF was N,N-dimethylformamide;
[0060] The precursor solution was spin-coated on the HTL surface at 6000 rpm for 15 s;
[0061] Then, a 40 mg / ml MAI solution was spin-coated in isopropanol at a speed of 4000 rpm for at least 45 seconds;
[0062] After spin coating, annealing was performed in air for 30 minutes to form a perovskite active layer 2;
[0063] The preparation method of the HALS-770 intermediate layer 6 comprises:
[0064] HALS-770 was dissolved in toluene at a concentration of 1.5 mg / ml. HALS-770 is di(2,2,6,6-tetramethyl-4-piperidinyl) azelaic acid ester;
[0065] The solution is spin-coated on the perovskite film, specifically on the electrode deposition layer 5, at a spin-coating speed of 6000 rpm for at least 30 seconds;
[0066] After spin coating, annealing was performed at 80°C for at least 3 minutes to form a HALS-770 intermediate layer 6;
[0067] The preparation method of the electron transport layer 3 and the buffer layer 4 includes:
[0068] Prepare PC61BM solution: dissolve 20 mg / ml PC61BM in chlorobenzene, where PC61BM is phenyl C61-butyric acid methyl ester;
[0069] Spin-coat the PC61BM solution on the perovskite layer at a speed of 2700 rpm for at least 30 seconds to form an electron transport layer 3;
[0070] Prepare BCP solution: dissolve 0.5 mg / ml BCP in isopropanol;
[0071] Spin-coat the BCP solution on the PC61BM layer at a speed of 6000 rpm for at least 30 seconds to form a buffer layer 4;
[0072] The preparation method of the electrode deposition layer 5 includes: depositing a silver electrode on the BCP layer by thermal evaporation, and controlling the vacuum degree to be below 5.0×10-4Pa;
[0073] Compared with the prior art, this application has the following advantages:
[0074] 1. Improved stability:
[0075] The unencapsulated device retained more than 95% of its initial efficiency after being stored for 30 days under ambient conditions (humidity of approximately 25-50%).
[0076] In the maximum power point tracking (MPPT) test in the glove box, the device's T80 (time to maintain 80% of initial efficiency) exceeded 1400 hours, significantly higher than the original device;
[0077] Compared with untreated perovskite films, HALS-770 modified perovskite films have reduced surface defects, reduced non-radiative recombination, and improved carrier extraction and transport efficiency;
[0078] 2. Improved photoelectric conversion efficiency:
[0079] Pin structure perovskite solar cell using HALS-770 at 0.06cm 2 A photoelectric conversion efficiency (PCE) of 21.88% was achieved on an effective area of 1.50 m2.
[0080] At 4cm 2 On the effective area, the PCE of the perovskite solar module reached 19.07%;
[0081] The PCE of the nip structure device using HALS-770 is also significantly improved, 0.06cm 2 and 1.0cm 2 The devices achieved PCEs of 23.03% and 20.73%, respectively;
[0082] 3. Enhanced antioxidant and heat resistance:
[0083] The HALS-770 layer enhances the antioxidant capacity of the perovskite by forming NO· radicals, which react with superoxide (O2·-), thereby removing O2·-;
[0084] The HALS-770 layer prevents the volatilization of organic cations and the migration of Ag+ and I-, improves the thermal stability of the perovskite and slows down the destruction of the Ag electrode;
[0085] Thermal stability tests show that the HALS-770 modified perovskite film maintains good structure and performance after continuous annealing at 85°C for 56 days;
[0086] 4. Enhanced water stability:
[0087] Water contact angle tests and water stability tests showed that HALS-770 modified perovskite films exhibited better stability in water and water vapor exposure;
[0088] The hydrophobic alkyl chain of HALS-770 and the hydrophilic ether and carbonyl groups work together to increase the hydrophobicity of the perovskite film.
[0089] The technical solution of the present invention is described above in conjunction with specific implementation methods, but it should be noted that the above descriptions are only for explaining the solution of the present invention and cannot be interpreted in any way as a specific limitation on the scope of protection of the invention. Based on the explanation here, those skilled in the art can think of other specific implementation methods or equivalent replacements of the present invention without creative work, and they will all fall within the scope of protection of the present invention.
Claims
1. A highly weather-resistant perovskite battery, characterized in that: The perovskite cell includes a bottom layer, a perovskite active layer, a HALS-770 intermediate layer, an electron transport layer, a buffer layer and an electrode deposition layer, wherein the perovskite active layer is arranged on the bottom layer, the electron transport layer is arranged on the perovskite active layer, the buffer layer is arranged on the electron transport layer, the electrode deposition layer is arranged on the buffer layer, and the HALS-770 intermediate layer is arranged on the electrode deposition layer.
2. A highly weather-resistant perovskite battery according to claim 1, characterized in that: The preparation method of the bottom layer comprises: Substrate pretreatment: Place the ITO / glass substrate in an ultrasonic bath of deionized water, ethanol, acetone, and isopropanol in sequence for 15 minutes each time; After cleaning, the ITO / glass substrate was treated in UV-ozone for at least 15 min to remove organic contaminants on the surface; Prepare PTAA solution: dissolve 5 mg / ml PTAA in chlorobenzene and add 25 wt% F4-TCNQ for doping; Spin-coat the PTAA solution on the treated ITO / glass substrate surface at a speed of 4000 rpm for at least 30 seconds; After spin coating, the ITO / glass substrate was annealed at a temperature of 100° C. for at least 15 minutes.
3. A highly weather-resistant perovskite battery according to claim 1, characterized in that: The preparation method of the perovskite active layer comprises: A mixed precursor solution of 1.3 mol PbI2 and 0.3 mol MAI was prepared in DMSO and DMF; The precursor solution was spin-coated on the HTL surface at 6000 rpm for 15 s; Then, a 40 mg / ml MAI solution was spin-coated in isopropanol at a speed of 4000 rpm for at least 45 seconds; After spin coating, annealing was performed in air for 30 minutes.
4. A highly weather-resistant perovskite battery according to claim 1, characterized in that: The preparation method of the HALS-770 intermediate layer comprises: HALS-770 was dissolved in toluene at a concentration of 1.5 mg / ml; The solution was spin-coated on the perovskite film at a speed of 6000 rpm for at least 30 seconds; After spin coating, anneal at 80 °C for at least 3 min.
5. A highly weather-resistant perovskite battery according to claim 1, characterized in that: The preparation method of the electron transport layer and the buffer layer comprises: Prepare PC61BM solution: dissolve 20 mg / ml PC61BM in chlorobenzene; Spin-coat the PC61BM solution on the perovskite layer at a speed of 2700 rpm for at least 30 seconds to form an electron transport layer; Prepare BCP solution: dissolve 0.5 mg / ml BCP in isopropanol; The BCP solution was spin-coated on the PC61BM layer at a speed of 6000 rpm for at least 30 seconds to form a buffer layer.
6. A highly weather-resistant perovskite battery according to claim 5, characterized in that: The preparation method of the electrode deposition layer comprises: depositing a silver electrode on the BCP layer by thermal evaporation, and controlling the vacuum degree at 5.0×10 -4 Below Pa.